“Nomenclature changes, essence unchanged”: Peripheral prisons reform and refusal to alter deterrence for rehabilitation - Babatope Matthew Ajiboye; Ene Norah Awe; Olabambo Evelyn Akinyemi (Journal of Social Studies (JSS), 2021)
The study focused on the Nigerian correctional institution and its mandate at rehabilitating convicts in preparedness for life outside bar and by implication reintegrating reformed individuals who are believed to pose no further threat to serenity of the society. Nigerian Correctional Service, previously known as Nigerian Prison Service, like its peer institution in the world, is primarily saddled with the responsibility to correct and reform convicts with the intent of reintegration back to conventional society. However, in Nigeria, this idea is render null and void with the broad-spectrum conception that when a person is sentenced to serve a jail term, that ultimately signifies the end of his or her worth in the society. Hence, the paper interrogates the Nigerian Correctional Service as an institution vested with the priority of making convicts better individuals. Emphasis was placed on the purported reformation of the institution in 2019. A secondary source was used for data collection and the content analytical approach was adopted which led to inferences drawn and logical conclusion established. The work reveals problems of welfare, infrastructural decay, and congestion coupled with pseudo rehabilitation obtainable in the institution. The study recommends that the Nigerian criminal justice system deserve an overhaul.